Unravelling 5 decades of anthropogenic 236U discharge from nuclear reprocessing plants - Castrillejo, Maxi; Witbaard, Rob; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655; Richardson, Christopher A.; Dekker, Rob; Synal, Hans-Arno; id_orcid:0 000-0001-5621-3089; Christl, Marcus; id_orcid:0 000-0002-3131-6652 (Elsevier, 2020)
Marine biogenic materials such as corals, shells, or seaweed have long been recognized as recorders of environmental conditions. Here, the bivalve Cerastoderma edule is used for the first time as a recorder of past seawater contamination with anthropogenic uranium, specifically 236U. Several studies have employed the authorized radioactive releases, including 236U, from nuclear reprocessing plants in La Hague, France, into the English Channel, and Sellafield, England, into the Irish Sea, to trace Atlantic waters and to understand recent climate induced circulation changes in the Arctic Ocean. Anthropogenic 236U has emerged over recent years as a new transient tracer to track these changes, but its application has been challenged owing to paucity of fundamental data on the input (timing and amount) of 236U from Sellafield. Here, we present 236U/238U data from bivalve shells collected close to La Hague and Sellafield from two unique shell collections that allow the reconstruction of the historical 236U contamination of seawater since the 1960s, mostly with bi-annual resolution. The novel archive is first validated by comparison with well-documented 236U discharges from La Hague. Then, shells from the Irish Sea are used to reconstruct the regional 236U contamination. Apart from defining new, observationally based 236U input functions that will allow more precise tracer studies in the Arctic Ocean, we find an unexpected peak of 236U releases to the Irish Sea in the 1970s. Using this peak, we provide evidence for a small, but significant recirculation of Irish Sea water into the English Channel. Tracing the 1970s peak should allow extending 236U tracer studies into the South Atlantic Ocean. ISSN:0048-9697 ISSN:1879-1026